2010
DOI: 10.4070/kcj.2010.40.9.434
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Coronary Artery Disease as Detected by Coronary Computed Tomography Angiography in an Asymptomatic Population

Abstract: Background and ObjectivesPrimary prevention of coronary artery disease (CAD) has become a public health issue, according to increasing awareness of the substantial risks posed by asymptomatic atherosclerosis. The aims of this study were to determine the prevalence and characteristics of subclinical CAD using coronary computed tomography angiography (CCTA), and to evaluate the role of this advanced technology in identifying subclinical CAD in asymptomatic Korean individuals, compared with conventional risk stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 24 publications
0
15
0
5
Order By: Relevance
“…In a retrospective analysis of over 13 000 coronarographies, an isolated change in RCA was found in 6.5% of cases, while a similar lesion was present over five times more frequently in the left artery (34.7%) [14][15][16][17]. Enrico et al in a study of 73,282 deposits in angio-CT scans of coronary arteries presented similar results by showing that nearly half of them were located in the LAD, and every third in RCA and circumflex artery [18][19][20]. The analysis also showed that patients with severe aortic stenosis were less often diagnosed with coronary artery disease, which concerned both patients with ischemic heart disease with and without significant atherosclerotic lesions, as well as with multi-vessel disease, 17.3% (n = 50) vs. 26.5% (n = 69), p < 0.001 (including prior STEMI and NSTEMI), 7.6% (n = 22) vs. 23.5% (n = 61), p < 0.001 (Table II).…”
Section: Discussionmentioning
confidence: 93%
“…In a retrospective analysis of over 13 000 coronarographies, an isolated change in RCA was found in 6.5% of cases, while a similar lesion was present over five times more frequently in the left artery (34.7%) [14][15][16][17]. Enrico et al in a study of 73,282 deposits in angio-CT scans of coronary arteries presented similar results by showing that nearly half of them were located in the LAD, and every third in RCA and circumflex artery [18][19][20]. The analysis also showed that patients with severe aortic stenosis were less often diagnosed with coronary artery disease, which concerned both patients with ischemic heart disease with and without significant atherosclerotic lesions, as well as with multi-vessel disease, 17.3% (n = 50) vs. 26.5% (n = 69), p < 0.001 (including prior STEMI and NSTEMI), 7.6% (n = 22) vs. 23.5% (n = 61), p < 0.001 (Table II).…”
Section: Discussionmentioning
confidence: 93%
“…Косвенным критерием, отражающим степень коронарного атеросклероза, является количество кальция, содержащегося в сосудах сердца, так называемый коронарный кальциевый индекс (индекс Агатстона). Он используется для обнаружения и оценки субклинического атеросклероза даже в отсутствие симптомов у пациентов [28][29][30][31][32].…”
Section: обзор §unclassified
“…Известно, что количество кальция коррелирует с тяжестью атеросклероза у разных пациентов, а также с поражением различных сегментов артерий венечного русла одного и того же индивидуума [33]. Это подтверждается данными компьютерной томографии (КТ) [28][29][30][31][32].…”
Section: обзор §unclassified
See 1 more Smart Citation
“…The amount of coronary artery calcium correlates with plaque burden and the calcium score roughly reflects the magnitude of coronary atherosclerosis [ 8 ]. According to tomographic studies, higher spatial distribution of calcalcifications and plaques is found in the LAD, then in RCA, circumflex branch (LCx) and the left main stem (LM) in a decreasing order of frequency [ 9 13 ].…”
Section: Plaque Distributionmentioning
confidence: 99%